Hi, I solved this question 3 times and I get different answers.

−5(1 − 5x) + 5(−8x − 2) = −4x − 8x

Hi Snelu

In this question you are supposed to solve for x:

You may use different methods although you should get same answer, be careful when you perform multiplication.

Let’s start from the right hand side because we have like terms which makes our calculations simpler.

−5(1 − 5x) + 5(−8x − 2) = −4x − 8x (we add these terms)

−5(1 − 5x) + 5(−8x − 2)= -12x

(from left hand side, we remove the brackets by multiplying each term inside the brackets with outside term)

therefore we have;

-5 + 25x -40x-10= -12x

(add the like terms)

-15 -15x= -12x

(transpose -15x to right hand side, therefore -15x becomes 15x )

-15= 15x + (-12x)

-15= 3x

thus, x= -5

You can prove this by substituting -5 into the original expression, where you see x you put -5, you should get same values from both sides.